EXPLORATION OF MOBILE USERS WITH QUESTIONNAIRE METHOD AND OBJECTIVE AUDIOMETRY (OTOACOUSTIC EMISSION) - Daria Fedorchenko; Vyacheslav Didkovsky (Bogomolets National Medical University, 2020)
Background: The main purpose of study was to assess the impact of using mobile phones among young Ukrainians (age 17-25) on auditory system. We conducted a study using anonymous questionnaires and with using a method of objective audiometry (otoacoustic emission). Finally, we compared our results with results of studies which were conducted in Sweden and Finland. Those studies were first among all the others with assessment of association between amount of mobile phone use and frequency of headache, tinnitus or hearing loss at 4-year follow-up. Methods: The participants were chosen among volunteers (n=251). All of them received anonymous questionnaires. We made stratified sample by age, sex, type of phone used, duration of phone calls, using of headphones during calls, symptoms appearing after using cell phone (headache, tinnitus, hearing loss). Results: The age of respondents was 17-25 years (32,3% - 22 years, 13,1% - 19 years, 12,4% - 20 years, 10,8% - 23 years., 8,4% - 21 years., 8% - 18 years, 7,6% - 17 years, 2,8% - 24р., 2,8% - 25 years). Due to this data the median age of participants was 22 years. Sex: female - 74.3%, male - 25.7%. Most of participants were using mobile phones (99.2%). 51.8% of respondents were always using headphones during phone calls, 8.8% - never used headphones during phone calls, 39,4% - were rarely using headphones during phone calls.  We assess the association between mobile phone use and appearing symptoms after phone calls. 3.6% of respondents reported a headache after phone calls, 96.4% were free of this symptom after phone calls. 58.2% reported headache at least once a week, 41.8% - were free of this symptom. 42.2% of respondents reported tinnitus: 1.6% reported tinnitus every day, 4.8% once in 2-3 days, 35.9% reported this symptom rarely (less than once a week). 57.8% of respondents were free of tinnitus. 21.5% of respondents reported hearing loss, 78.5% were free of hearing loss. Most of respondents associate headache with fatigue, sleep deprivation, stress, weather change, sleep disorders, arterial hypertension, hunger, frequent phone calls. Respondents who complained of hearing loss were offered to pass objective audiometry (optoacoustic emission).6 respondents took part in this examination. In 85 ears of respondents (71%) who complained of hearing loss it occurs on 8000 Hz. In 95 ears of respondents (79%) who complained of hearing loss it occurs on 5714 Hz. Pearson correlation coefficient between our results and results of Northern Europe studies was 0.935, suggesting a strong linear association.